Sistem Pendukung Keputusan Kelompok Untuk Penilaian Kinerja Unit Perusahaan Menggunakan Metode TOPSIS dan Borda (Studi Kasus: Perum Jasa Tirta 1 Malang) - Alysha Ghea Arliana; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Performance appraisal on company units is a process of assessment of the ability of a group unit members in completing tasks in order to determine the level of success achieved by the unit. However, the assessment of the performance of the company units conducted in Perum Jasa Tirta 1 Malang is still conventional, causing the assessment process to take time. In addition, in assessing the performance of a company units involving several people because each person will have different assessment weight. Therefore, a system or model is required to facilitate the assessment of the company's unit performance that is group decision support system using TOPSIS and Borda method. TOPSIS method used for decision making on the assessment of the performance of the company units performed by each decision maker. Borda method used for group decision making from the results of each decision maker. Based on the tests performed, the test scenario 1 result the highest or best accuracy is 81% with the best weight in the combination of 4,5,6 while the test scenario 2 with the best weight on all combinations is 83%.